Memórias do brincar e construção de subjetividades: uma experiência com alunas de um curso de magistério - CHARTIER, Getúlio Corrêa (2010)
Based on the methodological approach of action-research, this study examines play and playing memories as resources for subjective manifestations that include images, actions and expression of imaginary universes. Integrated in the formal educational process of a group of future female teachers, play experiences are analyzed as inciting situations which allow and provoke socialization associated not only to entertainment but, also, to conflict and discrimination episodes. The study privileges dialogues about how play integrates and stimulates perceptions, interpretations and reactions of the students collaborators, discussing and reflecting about teaching work as a proposal constructed through playing actions. The voice and circumstances of two students are emphasized in order to put in evidence the flows between memory and subjectivity and, furthermore, to underline the importance and contribution of playing in the re-creation of daily situations. In this sense, play establishes conditions of possibilities for reflecting and collectivizing experiences lived in family, school and other spaces